THE NEXUS BETWEEN URBANIZATION, LIVESTOCK, AND DEFORESTATION IN SOUTHEAST ASIA: EVIDENCE FROM PMG AND PANEL-CAUSALITY - Destiartono, Mohamad Egi (PATTIMURA UNIVERSITY, 2023)
Southeast Asia is one of the regions that has received a red report card related to forest management. This article intends to investigate the relationship between urbanization, livestock, and deforestation in Southeast Asia, as well as elaborate on STRIPAT's concept. This study uses panel data of 9 countries and 28 periods, obtained from the statistical publication of WDI, World Bank. This article applies the Pooled Mean Group (PMG) estimation and performs unit root, co-integration, and causality tests. The estimation results show that urbanization, GDP per capita, and livestock positively and significantly impact deforestation. The increase in the level of urbanization, GDP per capita, and livestock production will be followed by a decrease in forest cover area. In contrast, population density is not the driver of deforestation. In addition, this paper confirms bidirectional causality between urbanization and deforestation rates, as well as a unidirectional causality from income per capita to deforestation and from population density to deforestation. National development plans, urban development, and livestock expansion must be integrated with forest management to reduce deforestation rates